Distribution characteristics of soil active organic carbon at different elevations and its effects on microbial communities in southeast Tibet - Ran, Fanglin; Zhou, Chenni; Wang, Jianke (Frontiers in Microbiology, 2024)
Global mountain ecosystems have garnered significant attention due to their rich biodiversity and crucial ecological functions; however, there is a dearth of research on the variations in soil active organic carbon across altitudinal gradients and their impacts on microbial communities. In this study, soil samples at an altitude of 3,800 m to 4,400 m were collected from Sejira Mountain in the southeast Tibet, and soil active organic carbon components, soil microbial community diversity, composition and structure distribution and their relationships were systematically analyzed. The results revealed a non-linear relationship between the elevation and the contents of soil organic carbon (SOC) and easily oxidized organic carbon (ROC), with an initial increase followed by a subsequent decrease, reaching their peak at an altitude of 4,200 m. The Shannon diversity of bacteria exhibited a significant decrease with increasing altitude, whereas no significant change was observed in the diversity of fungi. The bacterial community primarily comprised Acidobacteria, Proteobacteria, Chloroflexi, and Actinobacteriota. Among them, the relative abundance of Proteobacteria exhibited a negative correlation with increasing altitude, whereas Actinobacteriota demonstrated a positive correlation with elevation. The fungal communities primarily consisted of Basidiomycota, Ascomycota, and Mortierellomycota, with Ascomycota prevailing at lower altitudes and Basidiomycota dominating at higher altitudes. The diversity and composition of bacterial communities were primarily influenced by altitude, SOC, ROC, and POC (particulate organic carbon). Soil carbon-to-nitrogen ratio (C/N), dissolved organic carbon (DOC), and available phosphorus (AP) emerged as key factors influencing fungal community diversity, while POC played a pivotal role in shaping the composition and structure of the fungal community. In conclusion, we believe that soil active organic carbon components had a greater impact on the bacterial community in the primary forest ecosystem in southeast Tibet with the elevation gradient increasing, which provided a theoretical basis for further understanding of the relationship between the microbial community and soil carbon cycle in the plateau mountain ecosystem under the background of climate change.